Achados do imaginário : o consumo da faiança fina em Uruguaiana no final do século XIX - Silva, Jeremyas Machado (2012)
The objective of this research is to understand the consumption of fine earthenware European on the western border of Rio Grande do Sul, from the end of the nineteenth century until the second decade of the twentieth century considering the values approach and meanings that these products had integrated to its materiality. The ceramic products studied did not have only one functional trend and were not empty of meanings. In this dissertation, the ceramic products are regarded as symbols that carry a social definition being able to express the values and identities of fashion. The consumption of fine faience in Uruguaiana in this period includes port movement, trade and smuggling that involves the social imaginary of Brazil's border with Argentina and Uruguay, in addition, the region is experiencing a moment of political, social and economic development. Thereby, we attempted to relate to the study of material culture analysis of documents, photographs and advertisements in local newspapers belonging to the historical period researched. Thus, it was possible to establish a deep interdisciplinary relationship, analyzing the archaeological, ethnological, historical sources and understanding through them, of the habits and the symbolic representations of society in Uruguaiana.